PROSPECTS OF 199TL-CHLORIDE AND 99MTC-MIBI SCINTIGRAPHY IN THE INDICATIONS OF BONE AND SOFT TISSUE SARCOMAS - A. P. Kurazhov; V. D. Zavadovskaya; E. L. Choynzonov; M. A. Zorkaltsev; O. Yu. Kilina; E. M. Slonimskaya; Yu. I. Tyukalov (Сибирский онкологический журнал)
Capabilities of 199Tl-chloride and 99mTc-MIBI scintigraphy in the non-nonspecific indications of bone and soft tissue sarcomas in overall 31 patients (34 lesions) were studied. Sensitivity of these methods in the detections of neoplasms reached 96.0 % and 100.0 %, respectively. It described positive, negative and mixed types of sarcomas visualizations on the both 199Tl-chloride and 99mTc-MIBI scintigraphy. There are preconditions for the 199Tl-chloride scintigraphy in the successful differentiations between bone and soft tissue sarcomas and benign tumors or non-tumor diseases, primarily inflammations.